2017
DOI: 10.1038/s41598-017-12418-z
|View full text |Cite
|
Sign up to set email alerts
|

Melt layer erosion during ELM-like heat loading on molybdenum as an alternative plasma-facing material

Abstract: Transient events that occur during plasma instabilities in fusion reactors impart large heat fluxes onto the surrounding plasma-facing components (PFCs). Erosion and splashing of PFCs can contaminate the plasma and shorten material lifetime. Although tungsten is currently considered the most promising candidate material for future PFCs, concerns over the thermal shock performance during type-I ELMs (transient events expected in fusion devices) necessitate the study of other comparable materials. ELM-like heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Figure 5b displays a drop of the ejected metal fallen and re-solidified in a zone near the crater. Sinclair et al [16] demonstrated that the surface melting of Mo begins when the energy density reaches a value of ~1.0 MJ•m −2 and that the droplet formation and boiling starts from ~1.4 MJ•m −2 , namely values much lower than those involved in the present experiments.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Figure 5b displays a drop of the ejected metal fallen and re-solidified in a zone near the crater. Sinclair et al [16] demonstrated that the surface melting of Mo begins when the energy density reaches a value of ~1.0 MJ•m −2 and that the droplet formation and boiling starts from ~1.4 MJ•m −2 , namely values much lower than those involved in the present experiments.…”
Section: Resultsmentioning
confidence: 51%
“…Recently, molybdenum (Mo) has attracted increasing interest as a possible PFM alternative to W [12][13][14][15][16]. As shown in Table 1, Mo is a high-Z refractory metal with very good physical properties (density, melting point, boiling point, and thermal conductivity), even if it is a little inferior to W. On the contrary, the ductile to brittle transition temperature (DBTT) of Mo is much lower, and it exhibits a better resistance to thermal shocks [15][16][17]. Another relevant advantage of Mo to W is its behavior under prolonged irradiation by 14 MeV neutrons of a fusion power plant.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid cooling will accumulate a lot of stress in the metal. Once the surface faces even higher power-density transient plasma, when the surface stress reaches the critical limit, the growing crystallite is no longer resistant to plastic deformation, [45] which is evidenced by observed widening cracks left in FE-SEM after pulsed load treatment.…”
Section: Crystal Structure Evolution Detected By Gixrdmentioning
confidence: 99%
“…The computational models were greatly refined and enhanced to account for many relevant physics effects and realistic conditions. The HEIGHTS simulation package [30] that consists of several integrated models has continued to be developed over the years and applied to many melting problems [39][40][41][42]. The MEMOS-1.5D code that implements the shallow water approximation [43,44] was upgraded to MEMOS-3D [45] and more recently to MEMOS-U [46].…”
Section: Introductionmentioning
confidence: 99%